Drgania swobodne pasma płytowego o zmiennej grubości - Mateja, O. (Engineering Transactions, 1968)
The problem concerns the transverse free vibrations of a strip of plates with the thickness being variable along its axis. The solution has been obtained using the matrix of transposition. A numerical example is given.